(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study assessed the effectiveness of e-governance on public service delivery in Zanzibar. Specifically, the study examined the contribution of e-governance in improving the accessibility of public service, the impact of e-governance in facilitating resource utilization on the delivery of public service, and the effect of e-governance in enhancing accountability on the public service delivery in public Institutions with a focus on three key variables: accessibility, resource utilization, and accountability. Accessibility is critical in ensuring that more citizens can engage with digital services, while effective resource utilization enhances the system’s capacity to meet public needs and accountability, though slightly less impactful, is vital for maintaining public trust and transparency in service delivery. Using a quantitative approach data was collected from 70 respondents. The findings indicate that accessibility has the strongest positive effect on public service delivery, followed by resource utilization and accountability, all of which are statistically significant. Accessibility has the strongest positive impact on Public Service Delivery with a notable unstandardized coefficient (B = 0.675) and standardized coefficient (β = 0.456). This suggests that for every one-unit increase in ACB, there is a corresponding increase of 0.675 units in PSD. While Resource Utilization and Accountability have smaller coefficients than ACB, their effects are nonetheless statistically significant. Resource Utilization (B = 0.320, β = 0.287) has a stronger effect than Accountability (B = 0.245, β = 0.198), indicating that effective resource allocation is more closely tied to perceived service delivery than accountability mechanisms. The study concludes that improving digital access, optimizing resources, and enhancing accountability mechanisms are essential for the success of e-governance initiatives in public institutions. Recommendations for policy improvements and further research are provided to guide the continued development of e-governance systems for better public service delivery.